Eksperimentasi Pembelajaran Matematika Dengan Pendekatan Saintifik Berbasis Discovery Learning (Dl) Dan Problem Based Learning (Pbl) Ditinjau Dari Komunikasi Matematika (Kelas VIII Semester Genap Di MTs Negeri Karangmojo Tasikmadu Tahun Ajaran 2015/2016) - MUSTIKA, OEN, Dra. N. Setyaningsih, M.Si (2016)
This study aims to describe and analyze: (1) the effect of the approach scientificallybased Discovery Learning and Problem Based Learning on learning outcomes, (2) the influence of mathematics communication on learning outcomes, and (3) the interaction approach is scientifically based Discovery Learning and Problem Based Learning and communication of mathematics on learning outcomes. The population in this study were students of class VIII MTs Karangmojo Tasikamadu Academic Year 2015/2016 by 7 parallel classes. This research was quantitative with quasiexperimental research designs (quasi-experimental research) .Teknik sampling used in this study is a cluster random sampling. Data collection method used is the test and questionnaire as the principal methods and documentation as an auxiliary method. The analysis technique used in this study is a two-way analysis of variance was not the same. From the results of the study at 5% was obtained: (1) there is no influence approaches to scientific-based Discovery Learning and Problem Based Learning on learning outcomes, (2) no influence communication level mathematics students (high, medium, and low) on the results of students' mathematics learning , (3) there is an interaction between the scientific approach based Discovery learning and Problem based learning in terms of communication of mathematics on mathematics learning outcomes